The pathogenicity of splicing defects: mechanistic insights into pre‐mRNA processing inform novel therapeutic approaches. (13th November 2015) - Daguenet, Elisabeth; Dujardin, Gwendal; Valcárcel, Juan
Abstract: Removal of introns from pre‐mRNA precursors (pre‐mRNA splicing) is a necessary step for the expression of most genes in multicellular organisms, and alternative patterns of intron removal diversify and regulate the output of genomic information. Mutation or natural variation in pre‐mRNA sequences, as well as in spliceosomal components and regulatory factors, has been implicated in the etiology and progression of numerous pathologies. These range from monogenic to multifactorial genetic diseases, including metabolic syndromes, muscular dystrophies, neurodegenerative and cardiovascular diseases, and cancer. Understanding the molecular mechanisms associated with splicing‐related pathologies can provide key insights into the normal function and physiological context of the complex splicing machinery and establish sound basis for novel therapeutic approaches. Abstract : Mutations affecting pre‐mRNA splicing have been linked to various human pathologies. This review discusses recent insights into the molecular mechanisms of disease‐causing splicing defects, which may inform future therapies and enhance our understanding of complex splicing processes.